Solution approach for flexible production systems (FPS) based on productivity and economic metrics - Todić, Velimir; Banjac, Dragan (Journal of Production Engineering, 1993)
The determination of the production-economic effectiveness when using FPS for the production of a specific group of parts requires the use of appropriate productivity and economic indicators. This presentation highlights the possibility of assessing the production-economic effectiveness based on the analysis of production and economic indicators, which is feasible for both a representative subgroup and the entire group. Based on production and economic indicators, it is possible to evaluate technological solutions for FPS using known data, as well as the individual structural solutions for the production of a specific group of parts